How do you solve -4( 5t - 5) + 9t = 2t - 3−4(5t−5)+9t=2t−3? Algebra Linear Equations Equations with Variables on Both Sides 1 Answer Lucy Jun 13, 2018 t=23/13t=2313 Explanation: -4(5t-5)+9t=2t-3−4(5t−5)+9t=2t−3 -20t+20+9t=2t-3−20t+20+9t=2t−3 20-11t=2t-320−11t=2t−3 23=13t23=13t t=23/13t=2313 Answer link Related questions How do you check solutions to equations with variables on both sides? How do you solve 125+20w-20w=43+37w-20w125+20w−20w=43+37w−20w? How do you solve for x in 3(x-1) = 2 (x+3)3(x−1)=2(x+3)? Is there a way to solve for x without using distribution in 4(x-1) = 2 (x+3)4(x−1)=2(x+3)? How do you solve for t in 2/7(t+2/3)=1/5(t-2/3)27(t+23)=15(t−23)? How do you solve 5n + 34 = −2(1 − 7n)5n+34=−2(1−7n)? How do you simplify first and then solve −(1 + 7x) − 6(−7 − x) = 36−(1+7x)−6(−7−x)=36? Why is the solution to this equation -15y + 7y + 1 = 3 - 8y−15y+7y+1=3−8y, "no solution"? How do you solve for variable w in the equation v=lwhv=lwh? How do you solve y-y_1=m(x-x_1)y−y1=m(x−x1) for m? See all questions in Equations with Variables on Both Sides Impact of this question 1684 views around the world You can reuse this answer Creative Commons License